ANALISIS BIAYA SATUAN OPERASIONAL NON PERSONALIA BERBASIS STANDAR KEBUTUHAN KOMPETENSI DI SMK - Nurfidah; Purnamawati; Abdul Muis Mappalotteng (Universitas Negeri Makassar, 2023)
This research is a qualitative research with a Descriptive Observational Case Studies approach which aims to obtain the factual non-personnel operational unit cost average required for the Competency of Computer and Network Engineering Skills at SMK Negeri 2 Bone. The research samples were school principals, deputy principals, BOS treasurers, administrative staff, heads of computer and network engineering competency skills computer and network engineering (TKJ) skills competency teachers at SMK Negeri 2 Bone. Data collection techniques through interviews, observation, questionnaire techniques and documentation. The data analysis technique used is qualitative analysis of flowing or interactive analysis models. This model consists of three components of analysis, namely data reduction, data presentation, and drawing conclusions or verification. The results of the study show that the average non-personnel operational unit cost in fact required for the Computer and Network Engineering Skills Competency at SMK Negeri 2 Bone in 2023 is Rp. 168.409,300, - using the current year's calculations and the number of students is 103 people spread across Class X, Class XI and Class XII.